Assessing and Modeling Pasture Growth under Different Nitrogen Fertilizer and Defoliation Rates in Argentina and the United States. (1st March 2019) - Insua, Juan R.; Utsumi, Santiago A.; Basso, Bruno
Abstract : Core Ideas: Model‐based approach identified sets of adaptive practices for pasture management across seasons. Suitable combinations of N rate and residual heights can improve the use of N fertilizer and water. The increment in residual pasture mass and N fertilizer may be crucial for more efficient use of water. Pasture growth responses to residual leaf area increased with N fertilization. The objectives of this research were to (i) evaluate the effects of N fertilizer, irrigation, and residual pasture heights on pasture growth, (ii) validate the ability of the SALUS model to predict dynamics of pasture growth, and (iii) evaluate during long‐term period the effects of using different N fertilizer levels and defoliation strategies on pasture growth, N fertilizer use, and water use efficiency (WUE). Eight single‐season experiments were performed at plot scale (8 m 2 ) in Buenos Aires (Argentina, ARG) and Michigan. In ARG different N fertilizer rates (from 0–500 kg N ha −1 ) were imposed on both rainfed and irrigated tall fescue [ Lolium arundinaceum (Schreb.) Darbysh.] pasture during autumn, spring, and summer. In the United States, three residual pasture height treatments (30, 60, and 120 mm) were imposed on both tall fescue and ryegrass ( Lolium perenne L.) pasture in the spring and summer. The SALUS was parameterized to simulate tall fescue and ryegrass growth using soil, weather, and different pasture treatments previously tested in ARG and the United States. Results showed that the SALUS accurately represented the response of herbage mass to irrigation and added N in the ARG site (RMSE < 650 kg DM ha −1 ) and to differences in residual pasture heights in the U.S. experiment (RMSE < 509 kg DM ha −1 ). Ten‐year simulations (2000–2010) demonstrated that suitable combinations of N fertilizer and residual pasture heights can significantly improve the use of N fertilizer by ∼300% and water by ∼230% through increases in herbage production.